Developing best practice guidelines for oral cancer management in Malaysia / Aznilawati Abdul Aziz - Aznilawati, Abdul Aziz (2017)
Background: Quality of care at every stages of oral cancer management is crucial to achieve optimal cancer outcome and to improve quality of life of cancer patients. Enhancing the quality of care for oral cancer patients requires an evidence-based framework outlining the current and best practices in patient management. An evidence-based practice guideline can be used as a decision guide for oral cancer teams and cancer patients in selecting the best option of oral cancer care. Aim: The aim of the study is to develop a best practice guideline for oral cancer management in Malaysia (which includes the stages of diagnosis, treatment, and follow-up care) for use by healthcare professionals managing oral cancer patients in the country. Methods: The concept of ―Guideline Adaptation‖ was used in the development of the Malaysian guideline. The core methodologies used were reviewing of high quality evidence and adoption as well as adaptation of recommendations from the existing guidelines, blended with expert judgements from a multidisciplinary group. Following the Practice Guidelines Evaluation and Adaptation Cycle (PGEAC), the guideline development process consists of six steps: i) identify clinical areas to promote best practice, ii) literature search to identify existing guidelines, iii) assessment of the guidelines in terms of quality, currency, and content, iv) adopt or adapt guidelines for local use v) seek multidisciplinary specialists feedback and vi) finalising best practice guidelines. Results: Initially, fifteen potential existing guidelines were selected through a systematic literature search. Of the fifteen guidelines, three guidelines that were developed by the Comprehensive Cancer Network (NCCN), Belgian Health Care Knowledge Centre (BKCE) and Scottish Intercollegiate Guideline Network (SIGN) were selected based on their good performance in the quality assessment using the AGREE II instrument. As the currency assessment revealed that all the three shortlisted guidelines were still up-to-date, these guidelines were considered the most appropriate to be included in the development of the local guidelines. On the basis of content analysis, the expert panel agreed to adopt 81 recommendations from the three guidelines whereas 10 recommendations were accepted with modification and one new recommendation was added to the draft guidelines. The draft version of the Malaysian guidelines comprised three sections (Section 1: Introduction, Section II: Development of the guidelines and Section III: eighty-eight clinical recommendations and summary of the evidence) and an algorithm of the whole process of oral cancer management. In response to the specialists‘ feedback, some minor changes and an additional recommendation were made to the draft. The final 47-pages Malaysian guidelines comprised three similar sections as in the draft, eighty-eight recommendations, an algorithm, and clinical audit indictors for quality management. Conclusion: The comprehensive Malaysian guideline with a final number of 88 recommendations was produced through a rigorous process in an attempt to cover all aspects of oral cancer management. Adherence to the guidelines in managing oral cancer patients in this country is expected to improve the quality of care and health outcome of the cancer patients.